2014
DOI: 10.1097/ico.0000000000000238
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Posterior Astigmatism Measured With Scheimpflug Imaging

Abstract: Purpose: Our aim was to assess the corneal power, axis, and age dependence of the anterior and posterior corneal surfaces with Scheimpflug imaging.Methods: Patients older than 10 years without a history of ocular surgery, corneal diseases, contact lens wearing, or severe dry eye were enrolled. Data regarding the anterior and posterior cornea were analyzed by means of Scheimpflug imaging (Pentacam HR).Results: The median age was 46.8 years (range: 10.0-90.3), and involved 827 eyes of 827 patients. Posterior cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 27 publications
5
35
0
Order By: Relevance
“…The magnitude of posterior corneal astigmatism in the high-myopia group was –0.29 ± 0.17 D, which agrees well with the values recorded in normal eyes [10,13,16]. Among the different age groups, however, the mean posterior corneal astigmatism was higher in patients aged 40–50 years (–0.40 ± 0.20 D) than in the older two age groups (–0.25 ± 0.15 D, 51–60 years; and –0.28 ± 0.17 D, ≥ 61 years).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The magnitude of posterior corneal astigmatism in the high-myopia group was –0.29 ± 0.17 D, which agrees well with the values recorded in normal eyes [10,13,16]. Among the different age groups, however, the mean posterior corneal astigmatism was higher in patients aged 40–50 years (–0.40 ± 0.20 D) than in the older two age groups (–0.25 ± 0.15 D, 51–60 years; and –0.28 ± 0.17 D, ≥ 61 years).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have reported a mean magnitude of posterior corneal astigmatism of −0.30 D [10]. Furthermore, the anterior corneal surface shifted from with-the-rule (WTR) to against-the-rule (ATR) astigmatism with age, whereas the posterior corneal surface continued to show ATR astigmatism in most cases [1016]. Therefore, patient-specific posterior corneal astigmatism measurements are required to estimate total corneal astigmatism.…”
Section: Introductionmentioning
confidence: 99%
“…Anterior corneal astigmatism (AA) is the astigmatism value arising from the anterior corneal surface alone and calculated as the difference in simulated keratometry values (calculated using the standard keratometric index (1.3375) and the radius of anterior corneal curvature) between the steepest and the flattest meridians [1316]. …”
Section: Methodsmentioning
confidence: 99%
“…The posterior corneal astigmatism is defined as the difference in keratometry values between the flattest and steepest meridians, which were calculated using the radius of posterior corneal curvature and the refractive indices of the cornea (1.376) and aqueous humor (1.336) [1316]. …”
Section: Methodsmentioning
confidence: 99%
“…[19] Bastig does not perfectly match the back element of TCPR4astig because Bastig is the back keratometric, not refractive, measurement on a ring of 15°, not 4 mm, around the corneal apex. [7,8] Although TCRP4astig and Bastig are calculated using different methods, ray tracing and the paraxial formula, respectively, such differences do not have much effect in normal eyes. [26] However, paraxial formula would be invalid compared with ray tracing if the posterior surface profile of the cornea were altered by refractive surgery.…”
Section: Discussionmentioning
confidence: 99%